'Aid with Chinese characteristics': competitive and/or complementary?. Issue 6 (7th October 2021) - Gülseven, Yahya
Abstract: China's growing foreign aid program in recent years has sparked many debates on alternative development cooperation approaches and practices. 'Aid with Chinese characteristics' is often approached with skepticism in the West and considered as posing challenges to the traditional aid architecture. The more optimistic perspectives see China's emergence as a major donor in a more positive light because it offers an alternative development cooperation model for aid recipient countries, contesting the hegemony of the neoliberal development model. While analysts have mostly focused on whether 'aid with Chinese characteristics' is a good or bad alternative, few have questioned its novelty and its actual potential as an alternative development cooperation model. From a neo-Gramscian perspective, this study investigates to what extend China, as a major donor, differs from the traditional donors and in how far that its aid model can be understood as representing a counter-hegemonic alternative. The core argument of this study is that 'aid with Chinese characteristics' serves the overall objectives and interests of the neoliberal historical bloc, while at the same time it also plays a role in the increasing tensions and competitions within it, between China and the Western countries in the context of the global financial crisis.